Autism spectrum disorder, attention-deficit hyperactivity disorder and offending. Issue 2 (29th October 2015) - Sabet, Jessica; Underwood, Lisa; Chaplin, Eddie; Hayward, Hannah; McCarthy, Jane
Abstract : Purpose: – A wealth of research on autism spectrum disorders (ASD) and attention-deficit hyperactivity disorder (ADHD) has led to increased understanding and identification of each of these developmental disorders. Existing literature has sparked controversial discussions regarding whether aspects of ASD and ADHD predispose individuals to criminality. The purpose of this paper is to explore the link between these conditions and offending. Design/methodology/approach: – A review of the literature on ASD, ADHD and offending was undertaken. This paper looks at the particular focus of the literature on the involvement of individuals with ADHD and ASD within the criminal justice system. Findings: – There is some evidence of a link between ADHD and criminality. However, the relationship between ASD and offending is a little more difficult to ascertain. Complicating this further is the relatively unexplored subject of comorbid ASD/ADHD and criminal behaviour. This paper found that additional cognitive deficits and conduct problems are associated with comorbid ASD/ADHD, highlighting the need for further research and development of interventions. Originality/value: – This paper seeks to examine whether predictions can be made with regards to what offending behaviour may look like in an individual with comorbid ASD/ADHD. This paper reviews the literature on offending in relation to both disorders to examine whether predictions can be made with regards to what the offending behaviour of an individual with ASD and ADHD may look like.